2016
DOI: 10.1007/s11864-016-0429-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy of Resected Non-small Cell Lung Cancer: can We Move Forward?

Abstract: Twenty years ago, an individual patient data meta-analysis of eight cisplatin-based adjuvant chemotherapy (AC) studies in completely resected early stage non-small cell lung cancer (NSCLC) demonstrated a 13 % reduction of the risk of death favoring chemotherapy that was of borderline statistical significance (p = 0.08). This marginal benefit boosted a new generation of randomized trials to evaluate the role of modern platinum-based regimens in resectable stages of NSCLC and, although individual studies generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Furthermore, our data show that exosomal miR451a is an independent predictive factor for recurrence and prognosis in stages I, II, and III. It has been reported that about 21-55% of stage I, II, and III patients experience recurrence after curative surgery, and adjuvant chemotherapy was conducted on these patients [2][3][4]. For accurate individualized treatment, an effective biomarker for the selection of high-risk patients is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our data show that exosomal miR451a is an independent predictive factor for recurrence and prognosis in stages I, II, and III. It has been reported that about 21-55% of stage I, II, and III patients experience recurrence after curative surgery, and adjuvant chemotherapy was conducted on these patients [2][3][4]. For accurate individualized treatment, an effective biomarker for the selection of high-risk patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that the 5-year recurrence rates after curative surgery among NSCLC patients with pathological stage (stage) I, II, or III cancer are 21, DOI: 10.1159/000487006 36, and 55%, respectively [2]. To prevent recurrence, adjuvant chemotherapy was administered to patients with stage IB, II, and III cancer who underwent curative surgery [3,4]. Chemotherapy without certain selection criteria tends to lead to overtreatment of patients, which in turn leads to severe side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, more than 70% cases of NSCLC are diagnosed at an advanced stage 3 . Thus, only about 25–30% cases of NSCLC are suitable for an effective surgical resection 4 . Radiotherapy, chemotherapy and targeted therapy are recommended treatment options for advanced stage NSCLC 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Statistics indicate that 70%–80% of the drugs used for single combination chemotherapy of malignant tumors are platinum based. [ 31 ] Although platinum-based anticancer drugs have achieved great success, there are many obstacles to their clinical applications, such as low targeting ability, low side effect threshold, and drug resistance. [ 32 ] Furthermore, we found that the alcohol extracts of Antrodia camphorata showed good inhibitory effects on the proliferation of A549 cells [Supplementary Material: Figure S1].…”
Section: Discussionmentioning
confidence: 99%